Identifikasi Pemahaman Konsep Siswa pada Materi Termokimia Menggunakan Tes Diagnostik Three-Tier Multiple Choice - Suleman, Nita; Lukum, Astin; Rauf, Nuramna; Paputungan, Mardjan; Alio, La; Sukamto, Kostiawan (Universitas Negeri Gorontalo, 2023)
This research is descriptive qualitative research, which aims to determine students' concept understanding of thermochemistry in class XI SMA Negeri 1 Gorontalo. The instrument used was a Three-tier multiple-choice Diagnosis Test. The research subject used was class XI IPA SMA Negeri 1 Gorontalo, with a sample size of 42 students. The research data was obtained from students' answers to the Three-tier multiple-choice questions. The data was processed based on the pattern of student answers, which were then grouped into the categories of conceptual understanding, misconceptions, and not conceptual understanding. The results showed that students who understood the concept were 46.19%, misconceptions were 43.97%, and did not understand the concept by 9.84%.